PENYIRAMAN PUPUK OTOMATIS DAN MONITORING KELEMBAPAN RUANGAN DENGAN PENERAPAN METODE SMART FARMING PADA TANAMAN HIDROPONIK MENGGUNAKAN MIKROKONTROLER - Lukman Muhamad Syafii (CV. Multi Kreasi Media, 2024)
Smart farming is a system designed by combining control tools and control systems in the form of applications, where the system uses the concept of the internet of things. To be able to build an affordable and integrated smart farming system, a microcontroller is needed. Mycocontroller is the brain of a system that has been built through the design stage by inserting code. In monitoring the humidity of this hydroponic room, it uses the type of ESP8266 microcontroller that has been integrated with wifi. Humidity data is obtained from sensors that have been integrated with each other so that the system can determine the time to regulate humidity in the room. On the other hand, the control system can also water fertilizer automatically where in the microcontroller a time has been set to water the plants.